Design Tradeoff Between Flux Regulation Capability and DC Winding Induced Voltage in Hybrid Excitation Switched Flux Machine - Zhang, Wentao; Wu, Zhongze; Wang, Zhimian; Hua, Wei; Fan, Ying; Xu, Zhiyuan; Cheng, Ming (IEEE transactions on industry applications, 2025)
In hybrid excited switched flux (HESF) machine, the DC winding provides the magnetic field regulation capability. However, it is also affected by the parasitic effects of DC winding induced voltage due to the inductance harmonics. Firstly, the phenomena and principles of the design tradeoff between the DC winding induced voltage and flux regulation capability are investigated through the multi-objective optimization results and case study for the HESF machines. It is observed that the high flux regulation capability HESF machines inevitably suffer from high DC winding induced voltage pulsation, which can be primarily attributed to the magnetic saturation in the stator lamination. This issue arises from the strong interaction between PM flux-leakage and the DC winding flux-linkage. Then, guidelines for addressing the design tradeoff are proposed, including the slot pole number combination, PM material selection and the DC winding power supply methods. It is found that HESF machine with 12-stator-slot and 13-pole rotor could suppress the DC winding induced voltage by 61% . Additionally, ferrite magnet material could improve the flux regulation capability, although the torque density is reduced compared to the NdFeB material. Different DC winding power supply methods are also discussed for addressing the design tradeoff between the DC winding induced voltage and flux regulation capability. Finally, a HESF machine prototype is built and tested. All the FE analysis are verified and validated through the finite element analysis and experimental results.